Manajemen Badan Usaha Milik Pesantren Dalam Pemenuhan Kebutuhan Santri - Ella Nopranda; Syahrul Amsari (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2022)
This study aims to reveal how the analysis of the management of Islamic Boarding-Owned Enterprises (BUMP) in meeting the needs of students at the Mawaridussalam Islamic Boarding School, Deli Serdang Regency. The method used in this research is a qualitative method with the type of case study research. Data collection techniques used in this study were observation, interviews and documentation. While data analysis using data analysis used in this study is data reduction. The data validity technique uses the triangulation method. Based on research and data analysis, it is concluded that the management of Islamic Boarding School Owned Enterprises (BUMP) in meeting the needs of students at Mawaridussalam Islamic Boarding School has implemented a well-organized management function. Starting from the management functions of planning (planning), organizing (organizing), mobilizing (mobilizing), and supervision (Controlling). The implementation of the management function at the Pesantren-Owned Shop Business Entity at the Hubulo Islamic Boarding School is carried out, so that it can be seen that the fulfillment of student needs is going well.